status of the Hen Harrier, Circus cyaneus, in the UK and Isle of Man in 2010 - Hayhow, Daniel B; Eaton, Mark A; Bladwell, Stephen; Etheridge, Brian; Ewing, Steven R; Ruddock, Marc; Saunders, Richard; Sharpe, Chris; Sim, Innes M.W; Stevenson, Andrew (Bird study, 2013)
Capsule The fourth national survey of Hen Harrier showed that the population in the UK and the Isle of Man declined significantly between 2004 and 2010. Aim To estimate the size of the breeding Hen Harrier population (with associated 95% confidence intervals) in the UK and Isle of Man, constituent countries and Scottish regions, in 2010 and calculate population change since previous surveys in 1998 and 2004. Methods Complete surveys were made of 10-km squares likely to be occupied by breeding Hen Harriers in England, Wales, Northern Ireland and the Isle of Man, using standard methods developed for previous national surveys. In Scotland, a ‘census’ area was non-randomly selected for survey by volunteers, and randomly selected squares were surveyed in two strata covering the rest of the known range. Results The UK and Isle of Man Hen Harrier population was estimated at 662 territorial pairs (95% confidence interval (CI): 576–770), a significant decline of 18% since 2004. Scotland holds the bulk (76%) of the population (505 territorial pairs; 95% CI: 417–612), with smaller numbers in Northern Ireland (59 pairs), Wales (57 pairs), the Isle of Man (29 pairs) and England (12 pairs). Declines of 49% and 20% were observed in the Isle of Man and in Scotland, respectively, whereas the Welsh population increased by 33%. A significant decrease was recorded in numbers of pairs using young and mature plantation forest in Scotland. Conclusion The breeding population of Hen Harriers in the UK and Isle of Man declined between 2004 and 2010. Notable decreases in Scotland and the Isle of Man may be related to habitat change and illegal persecution. Illegal persecution continues to limit the population size of harriers in England to very low levels.